Efforts to maintain a 'just great' story: Lesbian parents' talk about encounters with professionals in fertility clinics and maternal and child healthcare services. (February 2014) - Malmquist, Anna; Nelson, Karin Zetterqvist
After lesbian couples have decided to become parents, their family-making journey entails a wide range of encounters with professionals in fertility clinics and/or in maternal and child healthcare services. The article presents the results of an analysis of 96 lesbian mothers' interview talk about such encounters. In their stories and accounts, the interviewees draw on two separate and contradictory interpretative repertoires, the 'just great' repertoire and the 'heteronormative issues' repertoire. Throughout the interviews, the 'just great' repertoire strongly predominates, while the 'heteronormative issues' repertoire is rhetorically minimized. The recurrent accounts of health services as 'just great', and the mitigation of problems, are meaningful in relation to a broader discursive context. In a society where different-sex parents are the norm, the credibility of other kinds of parenthood is at stake. The 'just great' repertoire has a normalizing function for lesbian mothers, while the 'heteronormative issues' repertoire resists normative demands for adaptation.